2016
DOI: 10.1515/saeb-2016-0130
|View full text |Cite
|
Sign up to set email alerts
|

Emotional or Rational? The Determination of the Influence of Advertising Appeal on Advertising Effectiveness

Abstract: In prevailing competition-based market economy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…In order to increase acceptance of innovative products, such as BFF, researchers have identified a variety of execution strategies utilized in advertising that vary from the use of information appeals, emotional appeals, and neural process evoking [ 29 , 30 ]. The studies were intended to investigate assorted feelings, such as rationale appeals [ 31 ], emotional appeals [ 32 ], and informational [ 22 ] as the most common appeals. Hence, the literature has found that the use of these adverting appeals is beneficial in influencing an individual’s attitudes towards innovative products.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase acceptance of innovative products, such as BFF, researchers have identified a variety of execution strategies utilized in advertising that vary from the use of information appeals, emotional appeals, and neural process evoking [ 29 , 30 ]. The studies were intended to investigate assorted feelings, such as rationale appeals [ 31 ], emotional appeals [ 32 ], and informational [ 22 ] as the most common appeals. Hence, the literature has found that the use of these adverting appeals is beneficial in influencing an individual’s attitudes towards innovative products.…”
Section: Introductionmentioning
confidence: 99%
“…It seems particularly important to look for such hidden relations in various practical areas. For example, factors affecting the perception and cognition of visual stimuli are a particular focus of marketing and neuromarketing (see [82][83][84][85][86][87]). Specifying reliable objects-attributes relations that underlie similarity perception could facilitate the design of more effective graphic marketing messages used in product packages that will stand out from their competitors or advertisements.…”
Section: Applicationsmentioning
confidence: 99%
“…Disebutkan jika iklan dan daya tarik pendukung memengaruhi positif serta signifikan pada brand awareness. Daya tarik rasional dan emosional pada iklan bisa memengaruhi brand awareness (Grigaliunaite & Pileliene, 2016). Berdasarkan penelitian tersebut, hipotesis yang dapat dikembangkan dalam penelitian ini adalah: H1: Daya tarik iklan berpengaruh positif dan signifikan terhadap brand awareness.…”
Section: Pendahuluanunclassified